A histological description of alpaca (Vicugna pacos) cheek teeth: Findings and anatomical variations in macroscopically normal molars - Proost, Kirsten; Staszyk, Carsten; Boone, Matthieu N.; Vogelsberg, Jörg; Josipovic, Ivàn; Vlaminck, Lieven; Chiers, Koen (Frontiers in Veterinary Science, 2022)
Scientific literature on veterinary dentistry in alpacas has historically focused on the description of tooth root abscesses. However, recent studies have shown a variety of other, sometimes preceding dental conditions to be widespread in this species. To allow the development and finetuning of treatment strategies in this species, a more thorough understanding of the underlying etiopathogenesis of dental disease is required. Histological studies focusing on normal dental and surrounding tissues might serve as a basis for this purpose. Nine teeth, extracted from 7 alpacas were collected. All samples were retrieved from animals that died or were euthanized for non-dental reasons. Histological sections were prepared at three different levels in each tooth and examined using light microscopy focusing on the assessment of pulp tissue, dentin, cementum, periodontal tissues and the apical region. The histological appearance of the investigated dental tissues in alpacas showed great similarities with other hypsodont species. However, a rather rare type of dentin called ‘vasodentin’ could be identified in all examined cheek teeth. Another species-specific finding was the extremely close proximity of varying neighboring tooth roots that seemed to be responsible for inducing massive resorptive lesions. The results of this study might contribute to a better understanding of the etiopathogenesis of some dental diseases in the alpaca.